CONTRIBUIÇÃO DAS COMUNIDADES DE PRÁTICA PARA O PROCESSO DE AUTO AVALIAÇÃO EM UMA INSTITUIÇÃO DE EDUCAÇÃO SUPERIOR DO SEGMENTO PRIVADO - Gustavo Tomaz Buchele (Universidade Federal de Santa Catarina, 2016)
In higher education, knowledge management is still a concept that lacks a natural explanation for emerging practices may dilute the existing institutional models. In this sense, communities of practice (CoPs) appear as subs tantial relevance instrument to building a culture of evaluation. Thus, the purpose of this article is to identify the extent to which CoPs can collaborate with the self - assessment process in a higher education institution. In order to consolidate the effo rt even sought to characterize the community of practice that is the object of study, the identification of gaps in the self - assessment process of the study institution, the discussion of the process that occurs through the CoPs and the submission of tende rs and management actions of knowledge that emerged from the practice of community activity that constituted the institution in question. With respect to methodology, it is a predominantly qualitative, descriptive study, bibliographic, documentary, through content analysis and case study. The results arising from the research, in turn, showed that communities of practice collaborate and enable dissemination of knowledge in a systematic and innovative way.